Verbally expressed humor translation strategy in audiovisual products: a systematic literature review - Tong, Man Yu; Abdul Halim, Hazlina; Sim, Ng Boon (Sciedu Press, 2024)
Verbally Expressed Humor (VEH) is a form of humor that through language, written or spoken, to create comic effects. VEH translation in audiovisual products has been a great challenge due to the cultural and linguistic gap in target culture, and the translation inaccuracy and bias bring confusion to audience. Besides, though various methods have been utilized in investigating VEH translation strategies in subtitling and dubbing, no agreed-upon strategy suggestion for each category of VEH. In the present study, systematic literature review methodology is applied to examine related studies published until 1 January 2024, sourced from Web of Science (WoS) collection and Scopus. 35 articles are selected under the guideline of PRISMA 2020 and eligibility criteria. In general, the study aims to examine research status on VEH translation in audiovisual products. Specifically, it tends to clarify what translation strategies are used in translating VEH. The review indicates that: 1) English has been explored most frequently as the source and target language in studies of VEH translation in audiovisual products. 2) The major humor type examined in the selected studies is wordplay. 3) The VEH translation can be guided by various translation strategies taxonomies, while the slight adaptation or change is usually required. 4) Gottlieb’s (1992) taxonomy of translation strategies has been extensively utilized in the translation of VEH. However, there remains an absence of a standardized set of translation strategies that can be universally applied to any specific category of VEH. The findings can discover research gap and future trends for researchers, providing VEH translation advice for translators.